Efforts to Reduce Stunting Incidents Through Strengthening Positive Parenting in the Family - Kartika Hajati; Arlinda Puspita Sari; Nur Amaliah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Stunting is a growth and development problem of child that caused by not fulfilling balanced of nutrition. One of the provinces with a high stunting prevalence rate is West Sulawesi Province (second highest in Indonesia). Therefore, various parties are trying to help deal with this problem, one of which is Tim Penggerak Pemberdayaan dan Kesejahteraan Keluarga (TP-PKK) of Mamuju Regency, as well as being a partner in this service. One of the reasons for the high number of stunting cases in Mamuju Regency is the lack of knowledge about positive parenting in the family. This is closely related to inappropriate eating patterns so that the nutritional needs of pregnant women, babies, and toddlers are not properly met. The community service team with partners tries to provide a solution through this community stimulus partnership program (PKMS), namely by providing an educational program by trying to reduce the incidence of stunting through strengthening positive parenting in the family. The target audience consists of newly married mothers, pregnant women, mothers with babies and toddlers, BKB cadres and team of PKK in Mamuju Regency. The stages of activities include: coordination with partners, preparation, implementation of education, monitoring and evaluation, and final reporting. The results of the activity showed that participants' understanding of efforts to deal with stunting incidents through positive parenting in the family and improving eating patterns increased after receiving counseling materials, besides those participants felt satisfied and got direct benefits from the activities that had been implemented.